Generating Creativity in Elementary School Teaching: A Case Study of Teacher Professional Development in Indonesia - Weran, Yohana Ina; Kuswandono, Paulus (Vision: Journal for Language and Foreign Language Learning, 2021)
Creativity plays an important role in education for both students and teachers. In this study, the researchers aim to investigate how teachers generate elementary students’ creativity in the classroom. The study involved ten elementary school English teachers from ten schools in Sintang, West Kalimantan, Indonesia. This descriptive qualitative study employed snowball sampling by which the researchers invited one teacher to participate in this study and later the teacher suggested other potential participants that could be considered as the research samples. In gathering the data, the researchers identified teachers’ perspectives in generating creativity using questionnaires and interviews. The questionnaires results were in the form of a Likert Scale and a diagram was employed to display the overall tendency. Further, interviews were descriptively analysed to support the results of the questionnaires. The results of this study demonstrated that in generating creativity in the classroom, the following criteria should be fulfilled: (1) students’ mistakes should be welcomed and accepted as important part of learning; (2) students are expected to perform not only by constructing novel ideas, but also creating a product (outcome) that facilitates their creativity in the classroom. Other results close to the previous two main points are related to open-ended and real-life (authentic) tasks, resources availability, the atmosphere of care, and the teachers as a guide. In this study, the researchers provide data about how elementary school teachers generate creativity for elementary school students. It is suggested that further research should nurture and provide an atmosphere of care and physical environment to generate creativity.